Signatures associated with homologous recombination deficiency and immune regulation to improve clinical outcomes in patients with lung adenocarcinoma - Shang, Xueqian; Qi, Kang; Liu, Xiangzheng; Liu, Qinghao; Zhang, Xining; Wang, Dongliang; Huang, Weiming (Frontiers in Oncology, 2022)
PARP inhibitors can be used to treat solid tumors that often have mutations in important homologous recombination (HR) genes, such as BRCA1/2. While other kinds of tumors could also experience HR deficiencies, including those associated with lung cancer, there is little information on the frequency of these occurrences. Homologous recombination deficiency (HRD) was used to induce particular DNA aberration profiles and related transcriptome alterations. Their presence can identify whether an HR deficiency is present or absent in a particular tumor sample, even without observed HR gene changes. From whole-exome sequencing data in lung adenocarcinoma obtained from TCGA, we obtained several mutational signatures associated with HRD and determined that these HRD-associated mutational signatures are related to genomic installability. We then constructed a prediction model, which found that 11 genes associated with HRD scores could be used as predictors of survival outcome in LUAD patients. These genes are related to PI3K-Akt, T cell receptors, and the Chemokine pathway. Other GEO datasets validated the survival prediction, which was independent of the PD1/PDL1 treatment. Collectively, our study provides transcriptome biomarkers of lung adenocarcinoma complementary to the HRD score and introduces a novel method of identifying prognostic biomarkers of immunotherapy.